Influence of electrokinetic processing of a tropical soil on the PHs of the electrolytes - Ahmad, Kamarudin (Faculty of Civil Engineering, UTM, 2005)
The pH values of different anolytes and catholytes during electrokinetic (EK) processing of a tropical residual soil were investigated in laboratory. Four opened-anode and opened-cathode systems with different types of catholytes and anolytes were examined. Aluminium chloride, calcium chloride and phosphoric acid were used as electrolytes besides distilled water. Compressed soil samples, up to 90% of the maximum dry density at the optimum moisture content were subjected to a DC electrical potential of 30 V for 168 hrs. The pH values of the anolytes and catholytes were monitored continuously. The investigation showed that the pH values varied with time depending upon their initial values, the types of anolytes and catholytes and the systems employed. The measured pH values of the electrolytes were different from the theoretical values because of low efficiency of the EK experimental set up and complex electrochemical processes.